The lowest rung : voices of Australian poverty - Peel, Mark, 1959- (Cambridge University Press, 2003)
This is a fascinating and moving portrait of the people who are suffering in a more divided and less egalitarian Australian society. Based on the author's conversations with hundreds of people living in three areas commonly described as 'disadvantaged'- Inala in Queensland, Mount Druitt in New South Wales and Broadmeadows in Victoria - this is a book in which impoverished Australians, who are often absent from debates about poverty, tell their own stories.